How religion and morality correlate in age of society 5.0: Statistical analysis of emotional and moral associations with Buddhist religious terms appearing on Japanese blogs. (January 2020) - Nieuważny, Jagna; Masui, Fumito; Ptaszynski, Michal; Rzepka, Rafal; Nowakowski, Karol
Abstract: In this paper we analyzed how much religious vocabulary, in particular Buddhist vocabulary taken from the largest online dictionary of Buddhist terms, is present in everyday social space of Japanese people, particularly, in Japanese blog entries appearing on a popular blog service (Ameba blogs). We interpreted the level of everyday usage of Buddhist terms as appearance of such terms in the consciousness of people. We further analyzed what emotional and moral associations such contents generate. In particular, we analyzed whether expressions containing Buddhist vocabulary are considered appropriate or not from a moral point of view, as well as the emotional response of Internet users to Buddhist terminology. As a result of analyzing the data, we found out that Buddhist terms were in fact not absent as a theme from Japanese blogs and generated a strong emotional response. However, while the general reaction to several expressions using Buddhist terms was as expected, there were sometimes surprising twists in terms of social consequences, major discrepancies between what is perceived as ethically correct behavior between the Buddhist doctrine and the reasoning of the general population, as well as a considerate number of terms which have lost their original meaning and instead became slang expressions.